Aplikasi Prediksi Produksi Cabai dengan Algoritma C.45 untuk Dinas Pertanian Provinsi Aceh Berbasis Web - Afkar, M Kadafi; Wali, Muhammad; Imilda (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2024)
This research develops a chili production prediction application using the C.45 algorithm for the Aceh Province Agriculture Service. Weather data and chili prices from 2022-2023 are used to build a prediction model. After going through the data selection, preprocessing, and transformation stages, the C.45 algorithm model was successfully built and tested with new data. The results show a prediction accuracy of 84.03%. Furthermore, this model is implemented in the form of a web application which includes various features such as public pages, calculation of prediction results, graphs, and admin pages. Research shows that the use of the C.45 algorithm and this application has the potential to support agricultural decision making and planning in Aceh. Suggestions for further research include adding additional variables such as soil quality and socio-economic factors, as well as exploring remote sensing technology and other machine learning methods to increase prediction accuracy. Evaluation of the impact of using the application is also recommended to measure its effectiveness in supporting sustainable agriculture in Aceh